Penerapan Metode Quadtree pada Aplikasi Game Physics Puzzle - Widya Eka Putri (STMIK Budi Darma, 2020)
The introduction of media as a learning tool is the right and interesting thing in the framework of learning in remembering mathematical calculations to increase knowledge. The application of physics puzzle games is a medium that is run on the desktop as a means of entertainment as well as a means of learning. The research method in designing physics puzzle games is by the Quadtree method which checks collisions or collisions of two different objects in the two-dimensional game area by dividing the playing field to the same size then if there are two or more objects in the same area then the area will be subdivided into four equal sized parts until there are no objects in the same area. Providing interesting knowledge and entertainment to children, a physics puzzle game application is designed to provide a lesson in the middle of the game to easily remember math calculations